Characterization of pediatric mandibular fractures and their clinical management. Scoping review - Garcia Fuster , Consuelo (2025)
Objectives: Mandibular fractures in pediatric patients are relatively rare; however, understanding their characteristics enables early detection and appropriate referral, preventing complications and reducing costs for both public health and the patient. The objective of this research was to characterize pediatric mandibular fractures and their clinical management through a scoping review. Materials and Methods: The study was based on the Arksey and O’Malley method, verified using PRISMA-ScR. An electronic search for available evidence in English and Spanish was conducted in the scientific databases PubMed, Scopus, and EBSCO using the terms “mandible fracture” AND “pediatric.” Studies published between 2019 and 2024 were considered. Results: The search yielded 62 studies; duplicates were removed using the Rayyan artificial intelligence tool, resulting in 56 studies. After filtering by title and abstract, 29 articles were selected, and following a full-text review, 25 articles were included. Conclusions: The most common causes of pediatric mandibular fractures are motor vehicle accidents and sports- and play-related trauma, with males being the most affected demographic. The most frequently affected areas were the condyle and mandibular symphysis. A conservative management approach is generally preferred; however, the treatment strategy depends on factors such as age, displacement, and potential impact on growth and development. Although pediatric mandibular fractures are less common, their diagnosis and management should not be underestimated due to long-term complications. Conservative treatment is preferred, but it should always be tailored to the individual patient's needs.